A quasi experimental study on menstrual cup use: Women's experiences, satisfaction, and menstruation impact - Şeyma Kilci Erciyas; Yusuf Bulgan; İlknur Tankal (Anatolian Journal of Health Research, 2026)
Aim: This study aimed to evaluate women's experiences with menstrual cup use, their satisfaction levels, and the impact of menstruation on their lives. Methods: This quasi experimental mixed methods study was conducted with 34 women who were either employed or studying at a university in Türkiye. Participants were provided with menstrual cups following an educational intervention and asked to use them for at least two menstrual cycles. Data were collected using the Menstrual Cup Use Satisfaction Form, the Menstruation Impact Scale (MIS), and a semi-structured interview form. Quantitative data were analyzed using descriptive statistics and the Wilcoxon signed-rank test, while qualitative data were analyzed using Braun and Clarke's six-phase thematic analysis. Results: The mean age of participants was 32.76±6.77 years; 85.3% were married, and 58.8% held a bachelor's degree. The mean total pretest MIS score (38.32±9.19) decreased significantly to 33.88±9.46 after the intervention (p=0.003). All participants reported that menstrual cup use eliminated odor, was easy to clean, reduced environmental waste, and provided economic benefits. Overall, 85.3% expressed satisfaction and willingness to continue use; however, 55.9% reported difficulty with insertion and 58.8% with removal. Qualitative analysis revealed four themes: initial concerns, attitude change, use experiences, and environmental awareness.Conclusion: Menstrual cup use was regarded by women as a hygienic, economical, and environmentally friendly alternative. Despite initial concerns, high satisfaction rates were achieved after use. Difficulties experienced in insertion and removal can be overcome through education and practical applications. Nurses and midwives should integrate menstrual cup education into reproductive health counseling.